Contribution of Emotional Intelligence and Parental Social Support in Student Learning Achievement - Irsal Hadi; Netrawati Netrawati (Universitas Negeri Padang, 2020)
This study aims to analyze (1) learning achievement, emotional intelligence and social support of parents, (2) the contribution of emotional intelligence and social support both individually and collectively to student achievement behavior. This research uses descriptive quantitative method. The study population was 436 students of SMK Country 3 Padang. The research sample was 209 students who were selected by purposive sampling technique. The instrument uses a scale of emotional intelligence, and social support from parents and the results of the students' mid-semester value recap. The research data were analyzed using descriptive statistics, simple regression, multiple regression. The results of the study proved that: (1) emotional intelligence contributed 31.5% to student achievement, (2) parents' social support contributed 27.6% to student achievement, (3) emotional intelligence, shared parent social support contributed on student achievement as much as 33.4%. The implication of the results of this study can be used as input for making guidance and counseling service programs in improving student learning achievement.